Selected occupational burdens of masseur’s job – research report - Lewandowski, Andrzej; Siedlaczek, Marcin; Piekorz, Zuzanna; Zukow, Walery (Journal of Education, Health and Sport, 2024)
Introduction: Aim of the work is to analyze the burdensomeness of masseurs professional activities. Material and methods: Five massage standards were selected. The subjectively perceived level of physical and mental effort during massage was determined. The PWC170 test was used to measure physical fitness, and the intensity of physical exercise associated with the massage was determined. Statistics: Student's t-test and Fisher's test were used. Results: Women and men were characterized by medium/high levels of physical capacity (men: 3.70±0.82 l/min, women 2.21±0.34 l/min). Men's loads during massage was low (HR=87.49±1.748, which corresponded to 44.21±1.04% HRmax, VO2max=19.03±1.48, VO2=0.69±0.14 and 2.69±0.83 MET). The women performed work with moderate heart rate (HR=84.8±6.88, which corresponds to 44.18±3.67% HRmax, VO2max=18.99±5.24, VO2=0.43±0.162 and 2.16±0.86 MET). Respondents assessed their work as hard. The results suggest that massage and physical therapists had similar levels of fitness, but women differed significantly. Conclusions: Massage therapists of both sexes have similar opportunities to perform their profession. Difficulty in performing is caused the external working conditions and therapist strength.